High step‐up MIMO DC–DC power converter control‐based pole placement. (11th October 2022) - Radmanesh, Hamid; Maalandish, Mohammad; Pourjafar, Saeed; Khooban, Mohammad‐Hassan
Abstract: This paper introduces a new high step‐up multi‐input multi‐output (MIMO) DC–DC converter control‐based pole placement suitable for photovoltaic system applications. The suggested topology has a high stability current control. Low element number, high voltage conversion ratio, and low ripple input current are the main advantages of the proposed converter. The capability to use several energy resources with different voltage/current characteristics, increase the number of inputs and outputs arbitrary without duty‐cycle limitation, and control each input unit power switch independently are other advantages. The operation principle of the suggested topology, steady‐state analysis in continuous condition mode (CCM), and parameter design are analyzed. A comparison between the suggested topology and other converters is applied. Two‐input two‐output version of the suggested topology in 200 W at an operating 50 kHz switching frequency is analyzed. Finally, the Typhoon HiL‐404 emulating setup is applied to verify the performance and efficiency of the suggested high‐step‐up MIMO DC–DC power converter. Abstract : In this study, a new MIMO DC–DC converter control‐based pole placement is presented. High voltage gain and continuous input current are the main advantages of the suggested topology. Other benefits of the suggested topology can be considered: the ability of controlling the power flow of each input source arbitrary, a high voltage gain with the low number of elements, the possibility of having several outputs with different voltages, expandable to n ‐stage, and suitable dynamic response by controlling the proposed topology with the pole‐placement method. Finally, the accuracy operation of the suggested topology is performed in real‐time setup‐based Typhoon HIL‐404.